Pancreatic Mucinous Cystic Neoplasm Size Using CT Volumetry, Spherical and Ellipsoid Formulas: Validation Study - Chalian, Hamid; Seyal, Adeel Rahim; Rezai, Pedram; Töre, Hüseyin Gürkan; Miller, Frank H; Bentrem, David J; Yaghmai, Vahid (JOP. Journal of the Pancreas, 2014)
Context The accuracy for determining pancreatic cyst volume with commonly used spherical and ellipsoid methods is unknown. The role of CT volumetry in volumetric assessment of pancreatic cysts needs to be explored. Objectives To compare volumes of the pancreatic cysts by CT volumetry, spherical and ellipsoid methods and determine their accuracy by correlating with actual volume as determined by EUS-guided aspiration. Setting This is a retrospective analysis performed at a tertiary care center. Patients Seventy-eight pathologically proven pancreatic cysts evaluated with CT and endoscopic ultrasound (EUS) were included. Design The volume of fourteen cysts that had been fully aspirated by EUS was compared to CT volumetry and the routinely used methods (ellipsoid and spherical volume). Two independent observers measured all cysts using commercially available software to evaluate inter-observer reproducibility for CT volumetry. Main outcome measures The volume of pancreatic cysts as determined by various methods was compared using repeated measures analysis of variance. Bland-Altman plot and intraclass correlation coefficient were used to determine mean difference and correlation between observers and methods. The error was calculated as the percentage of the difference between the CT estimated volumes and the aspirated volume divided by the aspirated one. Results CT volumetry was comparable to aspirated volume (P=0.396) with very high intraclass correlation (r=0.891, P<0.001) and small mean difference (0.22 mL) and error (8.1%). Mean difference with aspirated volume and error were larger for ellipsoid (0.89 mL, 30.4%; P=0.024) and spherical (1.73 mL, 55.5%; P=0.004) volumes than CT volumetry. There was excellent inter-observer correlation in volumetry of the entire cohort (r=0.997, P<0.001). Conclusions CT volumetry is accurate and reproducible. Ellipsoid and spherical volume overestimate the true volume of pancreatic cysts. Image: 3-D CT image of a pancreatic tail mucinous cystic neoplasm